Technical and tactical soccer players' performance in conceptual small-sided games - Cristian Javier Ramirez Lizana; Riller Silva Reverdito; René Brenzikofer; Denise Vaz Macedo; Milton Shoiti Misuta; Alcides José Scaglia (Universidade Estadual Paulista (UNESP), 2015)
AbstractConceptual small-sided games (CSSGs) may be interesting as a methodology for training soccer players given its connection to the unpredictability that is inherent to soccer. Our aim was investigate, through videogrammetry, if the technical and tactical principles promoted through the adoption of distinct rules from two distinct CSSGs (maintaining ball possession; and progression to the target) would actually be achieved. The study included 24 athletes assigned to 6-player teams. Our data showed that the CSSGs' organising principles create situations with differing levels of difficulty that obey the propositions of maintaining ball possession and progression to the target, i.e., CSSGs permit systematic training on technical and tactical components in order to emphasize the concepts adopted in this study in games context. Our data credit the CSSGs for teaching technical and tactical lessons that, when coupled with adequate physical conditioning, can facilitate a player's capacity to merge thoughts and events in different situations.